Incidence Rates of Myomectomy-Related Mortality and Venous Thromboembolism in South Korea: A Population-Based Study - Yuk, Jin-Sung; Kim, Myounghwan (Frontiers in Medicine, 2022)
Background: Uterine leiomyomas are the most commonly observed pathologies, with an estimated prevalence of 4.5–68.6%. We aimed to calculate myomectomy-related mortality and venous thromboembolism incidence rates in the Republic of Korea. Methods: The data of patients who underwent myomectomy (2009–2018) were obtained from the Health Insurance Review and Assessment Service-National Inpatient Sample. The mortality rate after myomectomy was calculated using the leiomyoma diagnostic codes and myomectomy procedure codes. The incidence rates of venous thromboembolism, deep vein thrombosis, and pulmonary embolism were calculated using their diagnostic codes, with concomitant use of an antithrombotic agent during the same period or within 90 days after myomectomy. Results: The data of 23,549 women aged 15–55 years who underwent myomectomy were extracted. The myomectomy rate was 14.6 ± 0.1 per 10,000 patients. The average age was 39.39 ± 0.04 years. One patient who underwent myomectomy died; this patient did not have concomitant venous thromboembolism. The post-myomectomy mortality rate was 1.3 ± 0.8 per 10,000 patients. The incidence rates of venous thromboembolism, deep vein thrombosis, and pulmonary embolism after myomectomy were 5.7 ± 1.6 per 10,000 patients, 4.4 ± 1.4 per 10,000 patients, and 2.5 ± 1 per 10,000 patients, respectively. The conversion rate to hysterectomy was 2.9 ± 1.1 per 10,000 patients. Conclusion: The current mortality rate after myomectomy (0.013%) is substantially lower than that described in previous studies at the turn of the 20th century. The incidence of venous thromboembolism is also considerably lower than that in the general population worldwide.